Akibat Hukum Wanprestasi dalam Perjanjian Jual Beli Perangkat Lunak Microsoft - Bintang Sabda Ramadan; Iswi Hariyani; Pratiwi Puspitho Andini (Riau Law Journal, 2024)
The buying and selling relationship between consumers and business actors presents an engagement that results in an agreement in which both parties have a dispute which can be called performance on the agreement so as not to give rise to a dispute which can be called a dispute of default or broken promise. For example, the case between PT. Asaba Computer Center and PT. Eduspec Indonesia with a breach of contract dispute regarding the sale and purchase of software with the issuance of the East Jakarta District Court decision Number 361/PDT.G/2019/PN.Jkt.Tim. Decision on the lawsuit filed by PT. Asaba Computer Center regarding default or broken promises made by PT. Eduspec Indonesia, consumers who have made purchase orders to business actors who have agreed on the agreement that has been made, as well as the total costs and payment terms to complete all payments that have been agreed upon in the agreement that has been made, but the consumer consciously does not carry out the agreement that has been made. agreed or broken promises regarding the agreement. So the East Jakarta district court issued a decision declaring a breach of contract or broken promise to consumers.